Rapid body mass loss affects erythropoiesis and hemolysis but does not impair aerobic performance in combat athletes - Reljic, Dejan; Feist, Jonas; Jost, Joachim; Kieser, Meinhard; Friedmann-Bette, Birgit (Scandinavian journal of medicine & science in sports, 2016)
Rapid body mass loss (RBML) before competition was found to decrease hemoglobin mass (Hbmass) in elite boxers. This study aimed to investigate the underlying mechanisms of this observation. Fourteen well-trained combat athletes who reduced body mass before competitions (weight loss group, WLG) and 14 combat athletes who did not practice RBML (control group, CON) were tested during an ordinary training period (t-1), 1-2 days before an official competition (after 5-7 days RBML in WLG, t-2), and after a post-competition period (t-3). In WLG, body mass (−5.5%, range: 2.9-6.8 kg) and Hbmass (−4.1%) were significantly (P < 0.001) reduced after RBML and were still decreased by 1.6% (P < 0.05) and 2.6% (P < 0.001) at t-3 compared with t-1. After RBML, erythropoietin, reticulocytes, haptoglobin, triiodothyronine (FT3), and free androgen index (FAI) were decreased compared with t-1 and t-3. An increase occurred in ferritin and bilirubin. Peak treadmill-running performance and VO2peak did not change significantly, but performance at 4-mmol lactate threshold was higher after RBML (P < 0.05). In CON, no significant changes were found in any parameter. Apparently, the significant decrease in Hbmass after RBML in combat athletes was caused by impaired erythropoiesis and increased hemolysis without significant impact on aerobic performance capacity.
Gesehen am 17.06.2020